Strategi Guru PAI dalam Meningkatkan Kemampuan Membaca Al-Qur’an Peserta Didik di SDIT Generasi Cendekia Kec. Wanasalam Kab. Lebak-Banten - Masyitoh Fathonah Khoiriyah; Nan Rahminawati; Eko Surbiantoro (Bandung Conference Series: Islamic Education, 2022)
Abstract. Reading the Qur'an with makhrajul letters according to the correct rules of tajwid science is an obligation for every Muslim. To teach tajwid science in the learning process can be done by islamic religious education teachers. The technique that Islamic Religious Education teachers can do this is to plan learning in reading the Qur'an to students. At SDIT Generasi Cendekia, activities to improve reading the Qur'an and memorization are contained in the educational curriculum and provide motivation for teachers in improving the quality of the Qur'ani generation. This study aims to; (1) The program of improving the reading of the Qur'an and memorization, namely the difficulty of reading the Qur'an to students, then with this there is an effort by the school and teachers to carry out the process learning is used to learn the Qur'an in schools and outside of school kbm as well. (2) The steps taken by Islamic Religious Education teachers in improving the reading ability of classes IV, V, and VI, namely first, opening learning with tadaradus together. Second, the teacher recites verses of the Qur'an and then the learners imitate them. Third, students are given motivation and reminded not to forget to memorize. Fourth, reading the do'a finishes the lesson. (3) The method used by the teacher of Islamic Religious Education Iqro Method', in that method the teacher carries out a learning process about recognizing the letter hijaiyah and its pronunciation according to the letter makhrajul. The Tallaqi method, by making a circle below so that students are closer, then the Islamic Religious Education teacher reads 5-10 verses in reading, then students imitate what is read. (4) Factors faced by Islamic Religious Education teachers, namely, the principal, the family environment, students, and facilities and infrastructure. As for the inhibiting factors, namely the lack of awareness of parents, as well as the feeling of laziness that hits students. Abstrak. Membaca Al-Qur’an dengan makhrajul huruf sesuai kaidah ilmu tajwid yang benar merupakan kewajiban bagi setiap muslim. Untuk mengajarkan ilmu tajwid dalam proses pembelajaran dapat dilakukan oleh guru Pendidikan Agama Islam. Teknik yang bisa dilakukan guru PAI melakukan hal tersebut adalah dengan melakukan perencanaan pembelajaran dalam membaca Al-Qur’an terhadap peserta didik. Di SDIT Generasi Cendekia kegiatan peningkatan membaca Al-Qur’an serta hafalan tertuang dalam kurikulum pendidikan serta memberikan motivasi untuk para guru dalam meningkatkan kualitas generasi Qur’ani. Penelitian ini bertujuan untuk; (1) Program peningkatan membaca Al-Qur’an serta hafalan yakni adanya kesulitan membaca Al-Qur’an pada peserta didik, maka dengan hal tersebut adanya upaya pihak sekolah dan para guru untuk melakukan proses pembelajaran yang digunakan untuk belajar Al-Qur’an disekolah dan diluar KBM sekolah juga. (2) Langkah-langkah guru PAI dalam meningkatkan kemampuan membaca kelas IV, V, dan VI yakni pertama, membuka pembelajaran dengan tadaradus bersama. Kedua, guru membacakan ayat-ayat Al-Qur’an lalu peserta didik menirunya. Ketiga, peserta didik diberikan motivasi serta diingatkan untuk tidak lupa mnyetorkan hafalan. Keempat, membaca do’a selesai pelajaran. (3) Metode yang digunakan oleh guru PAI Metode Iqro', dalam metode itu guru melakukan proses pembelajaran tentang mengenali huruf hijaiyah dan pengucapannya sesuai dengan huruf makhrajul. Metode Tallaqi, dengan membuat lingkaran dibawah agar peserta didik agar lebih dekat, selanjutnya guru PAI membacakan 5-10 ayat dalam membaca, lalu peserta didik meniru apa yang dibacakan. (4) Faktor yang dihadapi guru PAI yakni, kepala sekolah, lingkungan keluarga, peserta didik, dan sarana dan prasarana. Sedangkan untuk faktor yang menghambat yakni minimnya kesadaran orang tua, serta rasa malas yang melanda peserta didik.